Waldenström macroglobulinemia and relationship to immune deficiency. Issue 11 (19th September 2021) - Levy, Anthony; Guidez, Stéphanie; Debiais, Céline; Princet, Isabelle; Bouyer, Sabrina; Dindinaud, Elodie; Delwail, Vincent; Systchenko, Thomas; Moya, Niels; Gruchet, Cécile; Sabirou, Florence; Bobin, Arthur; et al.
Abstract: Primary or secondary immune deficiency (ID) is a risk factor, although rare, to develop Waldenström macroglobulinemia (WM). We aimed to better understand the incidence of this occurrence in the real-life and the outcome of either entity. We conducted a review of 194 WM in the Poitou-Charentes registry and identified 7 (3.6%) with a prior history of ID. Across the 7 WM with ID, 4 progressed to active WM disease and required treatment for WM with a median time between WM diagnosis and the first treatment of 1.5 years (range 0–3). The median time from ID to WM occurrence was 8 years (1–18). WM could develop from ID, although a rare event. Our first action was to systematically decrease immunosuppression with long-term control of ID. Half of indolent WM remained indolent despite ID and for remaining WM none appeared of poor risk WM.